Development of fiber-based piezoelectric sensors for the load monitoring of dynamically stressed fiber-reinforced composites. (10th March 2023) - Le Xuan, Hung; Haentzsche, Eric; Nocke, Andreas; Tran, Nguyen Hoai An; Kruppke, Iris; Cherif, Chokri
Abstract: Continuous load monitoring of fiber-reinforced composites represents a complex challenge for the composite sector. In this paper, the development and characterization of piezoelectric sensors for structural health monitoring applications based on polyvinylidene fluoride (PVDF) are presented. The basic sensor structures are melt spun bicomponent filaments in a core-sheath configuration. The core is a volumetric mixture of polypropylene (PP) and Pre-Elec PP, a PP-compound modified with carbon black. The sheath is made of PVDF. Three variants with increasing volumetric Pre-Elec ratio in the core (50 vol.%, 60 vol.% and 70 vol.%) are manufactured and analyzed by conducting optical and resistance measurements as well as tensile tests. In the subsequent process step, the bicomponent filaments are braided with copper fine wires. The PP core and copper braiding of the coaxial tricomponent yarn are used as inner and outer electrode, respectively. By generating an electrostatic high voltage field between these electrodes, the PVDF interlayer is subjected to contact polarization to initialize the piezoelectric effect. The piezoelectric characteristics and thereby the sensory potential of the produced sensor yarns are quantified and analyzed on the fiber and composite scale by investigating their piezoelectric behavior during cyclic tensile tests. The results of the different sensor yarn variants are compared with each other by evaluating the measured voltage signal as a function of the induced cyclic stresses.